2008
DOI: 10.1111/j.1600-051x.2007.01173.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analyses on C‐reactive protein in relation to periodontitis

Abstract: There is strong evidence from cross-sectional studies that plasma CRP in periodontitis is elevated compared with controls. There is modest evidence on the effect of periodontal therapy in lowering the levels of CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
536
11
25

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 632 publications
(640 citation statements)
references
References 88 publications
45
536
11
25
Order By: Relevance
“…Although the levels of CRP did not decrease significantly, the mean decrease after 12 months (0.45 g/L) is comparable to data presented in a recent meta-analysis [18]. Whether CRP really is an independent risk factor for CVD remains debatable [19], however studies have shown that even small differences in CRP concentrations can reflect the risk of developing CVD [20].…”
Section: Discussionsupporting
confidence: 76%
“…Although the levels of CRP did not decrease significantly, the mean decrease after 12 months (0.45 g/L) is comparable to data presented in a recent meta-analysis [18]. Whether CRP really is an independent risk factor for CVD remains debatable [19], however studies have shown that even small differences in CRP concentrations can reflect the risk of developing CVD [20].…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, there is a positive correlation between periodontal disease and obesity, hypertension, hyperlipidemia, or hyperglycemia (Zhou, Zhang, Liu, Zhang, & Li, 2015), although the molecular mechanisms of these relationships are unclear. Periodontitis is a low‐grade systemic inflammation that is reported to cause elevated systemic levels of inflammatory mediators such as C‐reactive protein and interleukin‐6 (Paraskevas, Huizinga, & Loos, 2008). A number of studies have found a similar association between an increase of C‐reactive protein or interleukin‐6 and increased mortality in dialysis patients (Zhang et al, 2013; Zimmermann et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The panel adopted the nomenclature and definitions for terms used by 2001 International Sepsis Definitions [46,47] and alcohol [48] consumption, malnutrition [82,157], swallowing impairment with aspiration [45], chemotherapy-induced neutropenia [39,158,159], disruption of physiological barriers as a consequence of radiodermitis and mucositis [40,160], gingival pockets and dental caries [161][162][163][164], age [12,165,166], co-morbidities such as diabetes and chronic obstructive pulmonary disease (COPD) [166], and the presence of central venous catheters, gastrostomy and tracheostomy are at a higher risk of infections. Conference (i.e.…”
Section: Definition Of Sepsis Syndromementioning
confidence: 99%